Implementasi GLS (Gerakan Literasi Sekolah) Melalui Pengadaan Perpustakaan Mini di SDN-6 Madurejo Tahun 2018 - Sriwati Sriwati (Anterior Jurnal, 2019)
The School Literacy Movement is a movement in an effort to foster student character that strives for students to have a culture of reading and writing so as to create lifelong learning. This routine activity is carried out to foster students' interest in reading and improve reading skills. The reading material contains the values ​​of character, consisting of local, national and global wisdom, which are delivered according to the participants' development. Interest in reading is one of the keys to one's success in knowing and adding insights to his knowledge. Activities to increase reading interest must be held and promoted. In line with the rapid development of science and technology, the more in printing technology the more information stored in books. At all levels of education, reading ability becomes a priority scale that students must master. By reading, students will obtain various information that has never been obtained before.